Transformasi Pemikiran Tasawuf : Landasan Pembentukan Karakter Islami Generasi-Z - Arrasyid, Arrasyid; Nada Khori Anisah, Nada Khori Anisah; Raudatul Husna, Raudatul Husna (JURNAL AL-AQIDAH, 2023)
The purpose of this article is to explain the transformation of Sufism thinking as a basis for forming the Islamic character of generation Z. This research uses a qualitative descriptive method in the form of a literature study. The results of this research show the conclusion that all of the various challenges faced by Generation Z, the application of Sufism thinking with the concepts of Takhalli, Tahalli, and Tajalli is expected to provide a strong spiritual foundation. This not only helps them face life's problems, but also forms better character, enriches their spirituality and helps them find deeper and more meaningful meaning and purpose in life. In this way, Sufism thinking can become a strong foundation for Generation Z in facing all the problems and challenges in this modern era.